Specific distribution of cross-sectional area in each hamstring muscle of sprint runners and relationship between those and sprint performance - Kamino, K.; Maehama, R.; Kunimasa, Y.; Makino, A.; Sano, K.; Kijima, K.; Komi, P. V.; Ishikawa, M. (Japanese Journal of Physical Fitness and Sports Medicine, 2018)
The purpose of the present study was to examine characteristics of muscle anatomical cross-sectional area (CSA) for different regions from proximal to distal parts of each muscle of the hamstring muscles in high-level sprinters, and to examine the relationship with those and the sprint performance. The CSA of the semitendinosus (ST), semimembranosus (SM), biceps femoris long head (BFL) and biceps femoris short head (BFS) at the four different region of hamstring muscles for twenty sprinters (SPRINT) and twenty healthy male control subjects (CTRL) were measured by using B-mode ultrasonography. The measured regions were divided into four parts from proximal to distal parts (PRO1, PRO2, DIS2, DIS1). The results clearly showed that absolute CSA values in distal parts for all muscles together with PRO2 in ST were greater in SPRINT than in CTRL. When relative CSA values to the entire hamstrings muscles in each region were compared, only relative CSA at PRO1 in ST was greater in SPRINT than in CTRL, conversely, that at proximal regions in BFL and distal regions in BFS were smaller in SPRINT. In the relationships with sprint performance, the CSAs at PRO1 and PRO2 in ST and at PRO1 in SM were only related negatively. These results suggest that distal parts of hamstring muscles for SPRINT may be characteristics for sprint runners. However, the movements related to the specific hypertrophy (PRO1 and PRO2 in ST, PRO1in SM) may play important roles of the improvement of their sprint performance.